Supervisory Behavior and Employee Turnover: A Field Experiment - Krackhardt, David; McKenna, John F.; Porter, Lyman W.; Steers, Richard M. (Academy of Management Journal, 1981)
Specific supervisor interactions with tellers in 50 branches of a commercial bank were examined for their contribution to turnover rates. For those branches that instigated such actions, turnover was significantly lower than in the matched control groups. Moreover, actual implementation was found to be influenced by the efficiency level of the individual branches.